An old student remembers changes. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
went to the University of Singapore in 1965 and the university of Malaya in 1968. Forty years have changed not only the buildings on campus but the very perceived functions of education, the rhythm of the universities and the nuances of its meaning in society.